Marketing as a Direction of Managerial Activity in Pre-School Education - Leonida Pisоtska (Pedagogical Discourse, 2014)
In the content of the article the attention is paid to the meaning of marketing in managerial activity of pre-school education, the necessity of using marketing for the functioning and development of pre-school educational establishment has been proved. On the basis of the analysis and generalization of the results of scientific creation, the content, essence of the main notions of the research have been revealed, the term «management of pre-school education» has been introduced into the scientific circulation; it is also cleared out the factors on which development and improvement of pre-school education depend on. The worked out concept of marketing system of pre-school education, which includes 9 basic structural components is recommended to consideration. Against the background of conceptual bases, the principles, on which modern marketing activity in pre-school education is grounded, have been determined, and the main tasks of functional direction «Organization of System of Marketing in Pre-School Education and its Management» have been offered. The main phases of offering additional educational services under the conditions of pre-school educational establishment have been suggested. On the grounds of empiric research and comparative data of ascertaining and controlling experiments the conclusions about the expediency of using the suggested concept of marketing system of pre-school education have been made. The prospect of scientific researches on the mentioned problem has been planned.